Organophosphate Pesticide Residue in Fruits and Vegetables (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
The use of the pesticide which does not follow the procedure may potentially cause residue of pesticide to be left on vegetables and fruits sold in supermarkets and traditional markets. We aimed to find the pattern of pesticide usage and levels of residue found in plants. This study was an analytical observation with a cross-sectional design using detailed sampling procedure. We obtained the data of the pesticide residue concentration by conducting laboratory examinations on eight samples of cabbage and eight samples of tomatoes from traditional markets and supermarkets in the city of Solo. The data were tested using simple linear regression testing. The organophosphate measurement results showed no residues were detected, because it was below the Limit of Detection (LOD). We concluded that pesticides containing active substances were not used in the vegetables we tested or the active substances were no longer contained in the vegetables after harvesting.